Fungi are key players in extreme ecosystems. (June 2022) - Coleine, Claudia; Stajich, Jason E.; Selbmann, Laura
Abstract : Extreme environments on Earth are typically devoid of macro life forms and are inhabited predominantly by highly adapted and specialized microorganisms. The discovery and persistence of these extremophiles provides tools to model how life arose on Earth and inform us on the limits of life. Fungi, in particular, are among the most extreme-tolerant organisms with highly versatile lifestyles and stunning ecological and morphological plasticity. Here, we overview the most notable examples of extremophilic and stress-tolerant fungi, highlighting their key roles in the functionality and balance of extreme ecosystems. The remarkable ability of fungi to tolerate and even thrive in the most extreme environments, which preclude most organisms, have reshaped current concepts regarding the limits of life on Earth. Highlights: It has become evident that extreme environments are not only inhabited by archaea and bacteria; fungi are the most versatile phylogenetic lineage in the Tree of Life and can colonize/survive in all types of extreme habitats. Fungi often show a greater capacity for tolerance to stresses than prokaryotes and fungal diversity in extreme environments is higher than previously thought. The discovery of extreme fungi has been pivotal for major scientific discoveries in biology and in advancing the field of biotechnology. A combination of extreme-tolerant features and ecological and morphological plasticity make fungi key organisms in the search for the limits of life on Earth and in the Universe.